2020
DOI: 10.24095/hpcdp.40.3.04
|View full text |Cite
|
Sign up to set email alerts
|

At-a-glance - An update on positive mental health among adults in Canada

Abstract: This At-a-glance presents updated estimates for the Positive Mental Health Surveillance Indicator Framework for adults aged 18 years and older. Using data from the 2015 and 2017 Canadian Community Health Survey, we calculated the prevalence of positive mental health and associated determinants. Estimates for positive mental health outcomes for adults ranged from 68.1% to 87.1%. We also explored the associations between sociodemographic factors and positive mental health among adults in Canada. Our findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 1 publication
1
11
0
1
Order By: Relevance
“…Additionally, a study carried out in Portugal, which sought to identify the predictive and explanatory variables of self-perceived health and happiness, reported that gender and age were factors that influenced the level of happiness, but the greatest effect was exerted by income, that is, the lower the income, the lower the perceived happiness ( Silva, 2014 ). In the United States, it was reported that the inhabitants of rural areas, especially older adults, are under less favorable economic and health conditions and that this impacts their emotional well-being, but it is not an exclusive case in this country, as it has also been reported in other countries such as Canada ( Henning-Smith, 2020 ; Varin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, a study carried out in Portugal, which sought to identify the predictive and explanatory variables of self-perceived health and happiness, reported that gender and age were factors that influenced the level of happiness, but the greatest effect was exerted by income, that is, the lower the income, the lower the perceived happiness ( Silva, 2014 ). In the United States, it was reported that the inhabitants of rural areas, especially older adults, are under less favorable economic and health conditions and that this impacts their emotional well-being, but it is not an exclusive case in this country, as it has also been reported in other countries such as Canada ( Henning-Smith, 2020 ; Varin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…High SRMH included those who answered "Excellent" or "Very good". 11 Community belonging was assessed by asking, "How would you describe your sense of belonging to your local community?" with "Very strong", "Somewhat strong", "Somewhat weak" and "Very weak" as response options.…”
Section: Methodsmentioning
confidence: 99%
“…High community belonging included those who answered "Very strong" or "Somewhat strong". 11 Life satisfaction was assessed by asking, "Using a scale of 0 to 10 where 0 means 'Very dissatisfied' and 10 means 'Very satisfied', how do you feel about your life as a whole right now?" We examined life satisfaction as a numerical variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, na Psicologia predominam felicidade e bem-estar psicológico; nas Ciências Sociais, satisfação com a vida e bem-estar subjetivo, e na Epidemiologia, qualidade de vida, qualidade de vida em saúde e saúde mental positiva. Eventualmente, vários desses termos são usados ao mesmo tempo, caso do estudo canadense publicado em 2020, associado a um esforço de vigilância epidemiológica de saúde mental positiva, o qual utilizou cinco indicadores que se revelaram relacionados, mas independentes: autoavaliação da saúde mental, felicidade, satisfação com a vida, bemestar psicológico e bem-estar social 21 .…”
Section: Introductionunclassified